2016
DOI: 10.1016/j.chest.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Where You Live Matters

Abstract: Residence in a medically underserved area is associated with higher incidence and mortality rates of severe sepsis and represents a novel method of access-to-care adjustment. Traditional access-to-care surrogates, however, are poorly associated with sepsis mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 23 publications
1
36
1
Order By: Relevance
“…In their recent article, they found residence in an MUA to be associated with mortality in patients with severe sepsis, whereas there was no association with traditional zip code–based surrogates. 15 There are several possible reasons for the discrepancy with our findings. The composite MUA score captures additional factors that may negatively impact health care, which may have generated a significant association with mortality in a small-scale study.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…In their recent article, they found residence in an MUA to be associated with mortality in patients with severe sepsis, whereas there was no association with traditional zip code–based surrogates. 15 There are several possible reasons for the discrepancy with our findings. The composite MUA score captures additional factors that may negatively impact health care, which may have generated a significant association with mortality in a small-scale study.…”
Section: Discussioncontrasting
confidence: 91%
“…14 Most recently, Goodwin et al examined the association of residing in an MUA in South Carolina on the incidence and outcomes of sepsis. 15 They found an increased incidence of sepsis hospitalizations (8.6 vs 6.8 cases/1000 people, P < .01) as well as an increased risk of mortality after adjustment for severity of sepsis. These findings likely explain the uneven distribution of sepsis across zip code income quartiles seen in our analysis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Demographic data were not collected, and data on the broader school nurse population in South Carolina were unavailable. However, researchers have shown that 246 of 424 zip codes and approximately 43% of the population aged 20 years or older were medically underserved in South Carolina in 2010 ( 15 ). As such, school nurses support the health of students from many medically underserved areas in South Carolina.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis incidence and mortality are already higher in medically underserved regions. 22 Given the resources required to respond to the SEP-1 program, optimal performance may be beyond the reach of smaller hospitals, or even larger hospitals, whose resources are already stretched to their limits. Public reporting and pay-for-performance can be adisadvantage to hospitals caring for underserved populations.…”
Section: Discussionmentioning
confidence: 99%